Structure and temporal shifts in virulence of Pseudoperonospora cubensis populations in the Czech Republic. (24th May 2012) - Lebeda, A.; Pavelková, J.; Sedláková, B.; Urban, J.
<x xml:space="preserve">Abstract</x> The structure and temporal dynamics of the virulence of Pseudoperonospora cubensis (causal agent of cucurbit downy mildew) were studied in pathogen populations in the Czech Republic from 2001 to 2010. A total of 398 P. cubensis isolates collected from Cucumis (Cm.) sativus, Cm. melo, Cucurbita (Cr.) maxima, Cr. pepo, Cr. moschata and Citrullus lanatus were analysed for variation in virulence (pathotypes). Virulence was evaluated on a differential set of 12 genotypes of cucurbitaceous plants. All isolates of P. cubensis were characterized by their level of virulence (classified according the number of virulence factors, VF; low VF = 1–4, medium VF = 5–8, high VF = 9–12): high (75%), medium (24%) and low (1%). The structure and dynamics of virulence in the pathogen populations were expressed by pathotypes using tetrad numerical codes and a total of 67 different pathotypes of P. cubensis were determined. The most susceptible group of differentials was Cucumis spp., while the lowest frequency of virulence was recorded on Cr. pepo ssp. pepo, Ci. lanatus and Luffa cylindrica. A high proportion (c. 90%) of isolates was able to infect cucurbit species Benincasa hispida and Lagenaria siceraria, which are not commonly cultivated in the Czech Republic or elsewhere in central Europe. In the recent pathogen populations (2008–2010) there was prevailing frequency (70–100%) of isolates with high numbers (9–12) of virulence factors. 'Super pathotype' 15.15.15 was often observed in the study within the pathogen populations and was one of the four most frequently recorded pathotypes. Pseudoperonospora cubensis populations shifted to a higher virulence over time. From 2009 the pathogen population changed dramatically and new pathotypes appeared able to establish natural and serious infection of Cucurbita spp. and Ci. lanatus, which was not observed in 2001–2008. Generally, virulence structure and dynamics of P. cubensis populations are extremely variable in the Czech Republic.